When the guardian becomes the enemy: Targeting ATM in PTEN-deficient cancers - McCabe, Nuala (Mol Cell Oncol, 2015)
Ataxia telangiectasia mutated (ATM) is an important signaling molecule in the DNA damage response and inhibitors of ATM are under clinical development. We identified a synthetic lethal interaction between ATM inhibition and phosphatase and tensin homolog (PTEN) loss that was the result of increased oxidative stress. Inhibition of ATM therefore represents a novel strategy to target PTEN-associated cancers.